12
$\begingroup$

Wikipedia has a proof of the identity $$ H_{n} =\sum_{k=1}^{n} (-1)^{k-1} \binom{n}{k} \frac{1}{k}$$

http://en.wikipedia.org/wiki/Harmonic_number#Calculation

Curiously, there is also the identity

$$ \frac{1}{n} = \sum_{k=1}^{n} (-1)^{k-1} \binom{n}{k} H_{k} $$

Can the second identity be derived from the first one?

$\endgroup$
8
$\begingroup$

This is a consequence of binomial inversion. In general, if $f_{n}$ and $g_{n}$ are sequences such that $$f_{n} = \sum_{k=0}^{n}g_{k}{n \choose k}$$

then

$$g_{n} = \sum_{k=0}^{n}(-1)^{n+k}f_{k}{n\choose k}$$

Here I take sequences to be functions from $\mathbb{N} \rightarrow \mathbb{R}$ where I am using the convention that the natural numbers start at $0$.

The second of your identities can be proved from the first using binomial inversion by taking $$f_n = \left\{ \begin{array}{lr} 0 & : n = 0\\ H_{n} & : n > 0 \end{array} \right. $$ and $$g_n = \left\{ \begin{array}{lr} 0 & : n = 0\\ (-1)^{n-1}\frac{1}{n} & : n > 0 \end{array} \right. $$

Several proofs of binomial inversion are given in the answer I linked to.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

We have

$$(x+y)^n=\sum_{k=0}^n{n\choose k}x^{n-k}y^k$$

set $x=1$ and $y=-t$ we get

$$(1-t)^n=\sum_{k=0}^n{n\choose k}(-1)^k t^k=-1+\sum_{k=1}^n(-1)^k{n\choose k} t^k$$

Differentiate both sides with respect to $t$

$$-n(1-t)^{n-1}=\sum_{k=1}^n(-1)^k{n\choose k} k\ t^{k-1}$$

Now multiply both sides by $\ln(1-t)$ then $\int_0^1 dt$ and use the fact that $\int_0^1 t^{k-1}\ln(1-t)\ dt=-\frac{H_k}{k}$

$$\sum_{k=1}^n(-1)^{k-1}{n\choose k} H_k=-n\int_0^1 (1-t)^{n-1}\ln(1-t)\ dt$$ $$\overset{1-t\to t}{=}-n\int_0^1 t^{n-1}\ln(t)\ dt=-n\left(-\frac{1}{n^2}\right)=\frac1n$$


Bonus:

If we follow the same approach without differentiating we will have

$$\sum_{k=1}^n(-1)^{k-1}{n\choose k} \frac{H_k}{k}=H_n^{(2)}$$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ \begin{align} &\bbox[5px,#ffd]{\sum_{k = 1}^{n}\pars{-1}^{k - 1}{n \choose k}H_{k}} = -\sum_{k = 1}^{n}H_{k}\,\pars{-1}^{k}{n \choose n - k} \\[5mm] = &\ -\sum_{k = 1}^{n}H_{k}\,\pars{-1}^{k}\bracks{z^{n - k}} \pars{1 + z}^{n} = -\bracks{z^{n}}\pars{1 + z}^{n}\sum_{k = 1}^{n}H_{k}\,\pars{-z}^{k} \\[5mm] = &\ \bracks{z^{n}}\pars{1 + z}^{n}\,{\ln\pars{1 + z} \over 1 + z} = \bracks{z^{n}}\pars{1 + z}^{n - 1}\bracks{\nu^{1}}\pars{1 + z}^{\nu} \\[5mm] = &\ \bracks{\nu^{1}}\bracks{z^{n}}\pars{1 + z}^{n + \nu - 1} = \bracks{\nu^{1}}{n + \nu - 1 \choose n} = \bracks{\nu^{1}} {\Gamma\pars{n + \nu} \over \Gamma\pars{n + 1}\Gamma\pars{\nu}} \\[5mm] = &\ \bracks{\nu^{1}}\nu\, {\Gamma\pars{n + \nu} \over \Gamma\pars{n + 1}\Gamma\pars{\nu + 1}} = \bracks{\nu^{0}} {\Gamma\pars{n + \nu} \over \Gamma\pars{n + 1}\Gamma\pars{\nu + 1}} \\[5mm] = &\ {\Gamma\pars{n} \over \Gamma\pars{n + 1}\Gamma\pars{1}} = \bbx{\large{1 \over n}} \\ & \end{align}

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.